2012
DOI: 10.1007/s00266-012-9957-3
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Obtaining Platelet-Rich Plasma (PRP), Platelet-Poor Plasma (PPP), and Thrombin for Autologous Use

Abstract: This journal requires that authors assign a level of evidence to each article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 28 publications
0
60
0
3
Order By: Relevance
“…Furthermore, although the form of PRF was decided at the time of preparation, the form and timing of PPP can be adjusted for use through gelation, and mix easily synthetic materials in gel form. With few studies having been carried out for bone regeneration with PPP, 48,49 this study is of great significance as it demonstrates the effectiveness of PPP on bone formation.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, although the form of PRF was decided at the time of preparation, the form and timing of PPP can be adjusted for use through gelation, and mix easily synthetic materials in gel form. With few studies having been carried out for bone regeneration with PPP, 48,49 this study is of great significance as it demonstrates the effectiveness of PPP on bone formation.…”
Section: Discussionmentioning
confidence: 97%
“…A higher centrifugal force for the second spin was recommended to shorten the preparation time and increase platelet numbers. 25,26 However, high centrifugation will cause platelet fragmentation, which will result in the release of some growth factors during preparation and compromise bioactivity. 9 Dugrillon et al studied the influence of centrifugal force on growth factor release and found that platelet counts increased gradually as the centrifugal force increased from 400 to 1200 g. 27 However, the concentration of TGF-b showed a biphasic response with a significant increase from 400 to 800 g, but without further increase at 1000 and 1200 g 27 ; 800 g seems to be the optimal centrifugal force for the second spin.…”
Section: Preparation Of Prpmentioning
confidence: 99%
“…16,90 There are also methods and devices to generate thrombin from a single donation of plasma. 87,91 Several considerations must be taken in account when selecting the appropriate fibrin glue for scaffold fabrication (Table 3). Commercially produced fibrin glue is available at a standardized quality, whereas single-donor fibrin glue suffers from batch-to-batch variability.…”
Section: Fibrin Preparationmentioning
confidence: 99%